Shekhinah as 'shield' to Israel:1 Refiguring the Role of Divine Presence in Jewish Tradition and the Shoah. (September 2016) - Devine, Luke
The biblical, talmudic, midrashic, and mystical traditions, as well as contemporary Jewish feminist theologies, reveal a plethora of Shekhinah images. If tracked historically these readings, while diverse, reveal continuities even across traditions. These include Shekhinah 's 'immanence', 'presence', 'exile', and shared 'suffering'. Another vital continuity is Shekhinah 's function as protective 'shield'. Accordingly, in her gendered theology of the Shoah Raphael argues that Shekhinah was 'present but concealed in Auschwitz because her female face was yet unknowable to women'. Raphael's selectivist approach appropriates and de-contextualizes texts from the biblical, rabbinic, Zoharic, Lurianic and Hasidic traditions. For Raphael this methodology is necessary given the tradition's 'androcentric and patriarchal' underpinnings. This article's reading of Shekhinah 's role in the Shoah, however, differs from Raphael's theology. Indeed, while Raphael acknowledges the historical continuities of Shekhinah 's 'immanence', 'presence', 'exile', 'suffering' and protection, she justifiably claims that Auschwitz was not a 'place of protection'. This is because Raphael understandably refuses associate Shekhinah with the 'violent and abusive' God of the 'masculine Jewish tradition'. Yet a reading of the tradition(s), 'warts and all', reveals that Shekhinah 's presence but inability to protect the 'victims' is a break with precedent and requires explanation. This article therefore tracks Shekhinah 's protective role in Jewish tradition and history to suggest, using mystical texts, that the divine presence was sufficiently empowered to intervene in the Shoah and pleaded Israel's cause, but was powerless because the Holy One, blessed be He refused to 'consent'. In the process this article hopes to add another layer to Shekhinah 's story and to help 'bring her out of exile'.